HEAVY METAL ACCUMULATION IN ROOTS OF ТARAXACUM OFFICINALE WIGG - Komarova, Irina (My University, 2018)
Soil is an active acceptor for some elements, heavy metals in particular. Microelements are firmly sorbed and interact with soil humus layer. At the same time some plants are resistant to soil contamination and can be used as bioindicators. For this very reason the use of the most common urban flora species in the system of ecological monitoring enables to assess pollution level of various cities and industrial agglomerations.
Keywords: Phytoremediation; Heavy Metals; Тaraxacum officinale